Tun Sakaran Dandai : membina jati diri dalam perjuangan politik - Sakaran bin Dandai, Tun, 1930-; Hamzah, Amir, Tengku, 1911-1946; Chacho Haji Bulah, 1958- (Kota Kinabalu : Jabatan Cetak Kerajaan, 2007)
Autobiography of Sakaran Dandai, a politician and Chief Minister of Sabah from 1994 to 1995.
In Malay.
Includes bibliographical references (p. 203-204) and indexes.
Keywords: Sakaran bin Dandai, -- Tun, -- 1930-; Politicians -- Malaysia -- Sabah -- Biography; Sabah -- Politics and government